GEOLOGI, ALTERASI, MINERALISASI BIJIH, DAN KARAKTERISTIK FLUIDA HIDROTERMAL PADA ENDAPAN EMAS EPITERMAL SULFIDASI RENDAH DI DAERAH CIHONJE-PANINGKABAN, KECAMATAN GUMELAR, KABUPATEN BANYUMAS, PROPINSI JAWA TENGAH - , FAHMI HAKIM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research area is located in Cihonje and Paningkaban Village, Banyumas Regency, Central Java Province. The research area is found by many artisanal and small-scale gold miners (ASGM) are operating in that area. Based on that, researchers want to know the types and characteristics of deposits that produce gold. In the research area there are several vein orientation with the relative direction north-south, northwest-southeast and northeast-southwest. Host rock of the mineralization are turbidite volcaniclastic sedimentary rocks of the Halang Formation, consist of looping gradation of sandstone and siltstone unit which have a good porosity and permeability. While the geological structures which controls mineralization is an extension joints, Babakan Normal Left Slip Fault and Paningkaban Left Slip Fault. Dilational ore environment is known as the type of jogs in the form of en-echelon tension veins. Vein orientation which are most abundant of ore mineralization is the northwest â southeast vein direction. There are 4 zones of alteration: phyllic alteration (sericite-quartz-pyriteÂ±carbonateÂ± chlorite), argillic alteration (illite-smectiteillite/ smectite-carbonate-quartz-sericite-dickiteÂ±chlorite), sub-propylitic alteration (chloritechlorite/ smectite-smectite-carbonateÂ±quartzÂ±zeolite), and weak sub-propylitic alteration (chlorite/smectiteÂ±carbonate). Hydrothermal alteration zones that show high mineralization with the set of ore minerals such as native gold, electrum, native silver, pyrite, chalcopyrite, sphalerite, galena, arsenopyrite, cubanite, marcasite, covelite and tennantite is generally found in the argillic alteration zone. Hydrothermal structures were identified as massive vein, vein swarm, low angle veins, stockwork and disperse in diatreme breccia. Various types of vein textures are present, such as normal banded, cockade, crustiform, bladed carbonate, comb, and saccharoidal. Something interesting about this study is almost all of gangue minerals present are carbonate, and minor quartz with a high grade of gold (until 83 g/t Au). Stages of mineralization in the study area consists of stage 1 (fluidized breccia), stage 2 (quartz vein), stage 3 (carbonate-base metal), stage 4 (late carbonate), and the last stage 5 (supergene). The mineralization stages at temperatures ranging from 230~>300oC for hipogen stage and 150-210oC for supergene stage and estimated from fluid inclusion study of quartz and calcite ranges from 250-298oC. It is estimated the depth of mineralization is Â±890 meters below the paleosurface. The hidrotermal fluid is dilute, with an salinity 0,71 â 1,07 wt.% NaCl eq. from quartz, and 0,18 wt% NaCl eq. from calcite. It is speculated that these systems form as a result of the mixing of hydrothermal fluid (dominant by meteoric water) with CO2-rich waters. Based on the data and comparison to existing models, itâs indicates that the ore deposits types present in the research area is typical of low sulphidation epithermal especially carbonate-base metal-gold mineralization system.